DAMPAK PENGEMBANGAN CENTER POINT OF INDONESIA (CPI) TERHADAP PENCEMARAN DI SEKITAR PANTAI LOSARI - Fabelyn Gandryal Mistipa Avin; Cynthia Sampe Lolo (Riset Sains dan Teknologi Kelautan, 2023)
Center Point of Indonesia or commonly known as CPI is one of the icons of South Sulawesi, more precisely Makassar City. The reclamation and development of Center Point Of Indonesia is a major project that has a major impact on various aspects of human life. This paper aims to explain the impacts that may occur due to the reclamation and development of Center Point Of Indonesia, both positive and negative impacts. This massive renovation project is owned by the provincial government and is used as an integrated global strategic commercial park called Equilibrum Centerpoint Park. The land obtained from this reclamation is a quality development. However, the actual reality shows that there are still many people who have not implemented or practiced good waste management methods, as well as the unavailability of good filtering equipment from the Makassar City Government to avoid water pollution due to careless waste processing. The purpose of this study is to determine the impact of CPI (Center Point of Indonesia) development on water pollution around Losari Beach. In this case study, the research methodology used is a literature study. Through this research, the impact of CPI development on water pollution along Losari beach can be known from several readings. Uncontrolled waste disposal patterns or the government's lack of concern for water pollution are controversial issues. This mistake may be due to the impact of reclamation. Keywords: waste, impact, reclamation, center point of Indonesia